2020
DOI: 10.1177/1357633x20975257
|View full text |Cite
|
Sign up to set email alerts
|

Telepharmacy in oncology care: A scoping review

Abstract: Introduction Telepharmacy has the potential to enhance pharmacy services in oncology care, especially in remote areas. This scoping review explored the range, critical benefits and barriers of using telepharmacy services in oncology care. Methods The scoping review followed the Arksey and O’Malley’s five-stage framework to identify available evidence. PubMed, CINAHL, Embase, PsycINFO, Ovid MEDLINE and Scopus databases were searched for original research published between 2010 and 2020. The five dimensions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…These preliminary findings are consistent with other reports showing the benefit that telepharmacy can have on the overall well-being of various patient populations. 29 , 30 Beyond the physical and emotional toll that hospitalizations have on patients, there is also a financial toll on the health care system and patient alike.…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary findings are consistent with other reports showing the benefit that telepharmacy can have on the overall well-being of various patient populations. 29 , 30 Beyond the physical and emotional toll that hospitalizations have on patients, there is also a financial toll on the health care system and patient alike.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the dearth of information on patients’ willingness to pay for pharmaceutical procedures in general and for telepharmacy in particular, we consider that these aspects should be the subject of future pharmacoeconomic research. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, a meta-analysis of 21 articles from 2010 to 2020 has shown that telepharmacy has the potential to enhance pharmacy services in oncology care, including follow-up monitoring and counseling, intravenous chemotherapy and sterile compounding, expanding the availability of pharmacy services, and remote education. 4 Telepharmacy has been adopted in many parts of the world since 2001, especially in North America (the United States, Canada), [5][6][7][8] Europe (Spain), 9,10 and Oceania (Australia). 11 A study in all 7 states of the United Arab Emirates reported that telepharmacy has been used to provide pharmaceutical care to 19,974 patients over 4 months, which was 2 times higher than the number of patients cared by pharmacies that did not use this service.…”
Section: Introductionmentioning
confidence: 99%